The Relationship of Respondent Characteristics With the Implementation of Public Infection Prevention by Private Practice Midwife in the Work Area - Fatimah; Harahap, Maryam Latifah; Elvi Suryani (International Journal of Public Health Excellence (IJPHE), 2022)
The purpose of this study to determine the relationship between the characteristics of respondents with the implementation of postpartum prevention by Private Midwives Practice in the work area. The type of this research is descriptive correlative with cross sectional approach. Researchers used totally sampling technique. Analysis of data used chi-square. Based on the results of the study, 40 respondents were 22 - 39 years old, 23 people (57,5%), D - I midwifery education 22 people (55%), work experience 14 - 26 years old as many as 27 people (67,5 %), and less knowledge as many as 24 people (60%) .The results of data analysis of age relationship with the implementation of postpartum prevention obtained p value = 0.002 and OR = 11.40 means there is a significant relationship. Education with the implementation of postpartum prevention obtained p value = 0.032 and OR = 5.343 means there is a significant relationship and work experience with the implementation of postpartum prevention obtained p value = 0.063 and OR = 5.923 means there is no significant relationship. From the results of this study is expected to midwives as health workers to further improve the experience, knowledge, quality of service in prevention of infeksinifas.